Efficiency and pollutant emissions of an SI engine using biogas-hydrogen fuel blends: BIO60, BIO95, H20BIO60 and H20BIO95. (5th April 2018) - Nadaleti, Willian Cézar; Przybyla, Grzegorz; Vieira, Bruno; Leandro, Diuliana; Gadotti, Gizele; Quadro, Maurizio; Kunde, Érico; Correa, Luciara; Andreazza, Robson; Castro, Andrea
Abstract: Our planet has been experiencing abrupt climate changes in recent years. The major contributor to this phenomenon is, without doubt, emissions of gases derived from petroleum-based fuels, compared to their high consumption, especially diesel and gasoline. In Brazil, the sum of all motorized trips shows that more than half of them (60%) is based on public transport, with buses carrying 94% of all those who use this service. These vehicles, in their vast majority, use the technology of Compression Ignition (CI) engines. On the other hand, studies have shown that the country has a high biofuel production potential from various sources, such as landfills and hydroelectric plants, with an extensive production of biogas and hydrogen, that can be used, for example, in Spark Ignition (SI) engines. Nevertheless, SI engines have lower efficiency than CI engines. Part load operation of SI engines is conventionally achieved by the use of a throttle to control the airflow or air-fuel mixture into the engine. When operating at partial load the throttle causes exergy losses what affecting on decreasing engine efficiency. With the objective of analysing the emission of pollutants and the efficiency of conversion of fuel chemical energy, this work presents an analysis on the use of blends of hydrogen (H2 ), biogas (BIO60) and methane (BIO95) using an SI engine. The system was operated in partial load and the addition of H2 was an attempt to increase efficiency by reducing the pumping work through the throttle, once it was possible increasing the lambda value. The tests were performed at different ignition angles and air/fuel ratio. The value of ignition advance angle has been adjusted to obtain maximum Brake Thermal Efficiency (BTE) of the engine. It was possible to recognize that the addition of H2 allowed the combustion limits to be extended. On the other hand, reduced values of CO and NOx emissions could be achieved. Highlights: Methane-hydrogen fuel blends. Increase of indicated efficiency and Brake Thermal Efficiency. Reduction in NOx emissions in the lean mixture provided by the presence of H2 .